Safety & Benefits of Directly Observed Therapy with Rifapentine and Isoniazid for Latent Tuberculosis Infection – Less is More?. (4th October 2017) - Ha, Lawrence; Lam, Megan; Niknam, Negin; Schwartz, Rebecca; Rasul, Rehana; Mol, Loyce; Chin, Suzan; Epstein, Marcia; Hirschwerk, David; Revere, Elizabeth; Hayes, Lisa
Abstract: Background: Latent tuberculosis infection (LTBI) treatment is essential in preventing the reactivation of tuberculosis. We compared the clinical and demographic characteristics of patients that have completed traditional therapy with 9 months of isoniazid (9H) with those that have completed 3 months of rifapentine plus isoniazid using directly observed therapy (3HP), focusing on adverse effects, a barrier to completion that may contribute to discontinuation of therapy. Methods: We conducted a retrospective chart review (July 2013-March 2017) to compare the 9H group and 3HP group. Demographic and clinical variables were described by therapy type and groups were compared using Fisher's exact test or t-test, as appropriate. Results: Patients in the study sample ( n = 124) had a mean age of 49.8 (SD=14.8) years old. Approximately half received 3HP ( n = 64, 51.6%). Demographics in the 3HP and 9H groups were similar. Significantly more patients in the 3HP group completed treatment (81.3% vs. 61.7%, P < 0.0001). No patients were lost to follow-up in the 3HP group, 14 (23.33%) were lost in the 9H group. Gastrointestinal (GI) upset ( n = 16), elevated liver function tests (LFTs) ( n = 11), and headaches ( n = 9) were the most frequent side effects. Except for neuropathy and pancreatitis, all other adverse side effects had higher incidence in the 3HP group. Specifically, the incidence of GI symptoms (23.4% vs. 1.7%, P = 0.0003), weakness (9.4% vs. 0%, P = 0.028), and headache (14.1% vs. 0%, P = 0.003) were significantly higher in the 3HP group. Of the observed patients with adverse reactions that received 3HP, 88.24% ( n = 30) had them resolved within the first two weeks. Conclusion: The 3HP group had a higher completion rate and no loss to follow-up compared with 23% loss to follow-up in the 9H group, however, adverse reactions were significantly higher in the 3HP group. Closer weekly monitoring of the 3HP group could lend itself to capturing more adverse reactions, however, 88% of those adverse reactions resolved within the first two weeks of therapy. Liver function tests were not significantly different ( P = 0.2079) between the two groups, and were mildly elevated. We conclude that three months of rifapentine plus isoniazid for the treatment of LTBI may be a favorable option over the traditional 9 months of isoniazid in certain populations. Disclosures: All authors: No reported disclosures.